Case Report: Fatal Multiorgan Failure and Heterochronous Pneumonitis Following Pembrolizumab Treatment in a Patient With Large-Cell Neuroendocrine Carcinoma of Lung - Xie, Xiaohong; Wang, Fei; Qin, Yinyin; Lin, Xinqing; Xie, Zhanhong; Liu, Ming; Ouyang, Ming; Luo, Bihui; Gu, Yingying; Li, Shiyue; Gu, Dejian; Chen, Rongrong; et al. (Frontiers in Pharmacology, 2021)
Immune checkpoint inhibitor is an effective tumor therapy that has been introduced for the therapy of many cancers and severe immune-related adverse events are reported and relatively common. However, lethal simultaneous multi-organ failure has rare reported. Here, we described a patient who developed multi-organ failure including fulminant myocarditis, myasthenia gravis crisis, hepatic dysfunction and delayed pneumonitis after undergoing pembrolizumab therapy for lung large cell neuroendocrine carcinoma. In the treatment of this patient, we found that the implantation of cardiac pacemaker combined with high-dose steroids may be a feasible method to rescue myocarditis caused by immune checkpoint inhibitor. Consideration of delayed pneumonitis found after myocarditis in our patient, heterochronous adverse events should be notice.